Švedski u švengleskom - still going strong: Prilog proučavanju jezičnih dodira na primjeru anglicizama u švedskom - Antunović, Goranka (Array, 1992)
This work reports the results of an analysis of 1, 461 anglicisms in Swedish, all of which can be said to belong to the corpus of well-established loan words in contemporary Swedish. The analysis has focused on the adaptation of anglicisms at the four levels that are most affected in language contacts occuring in the country of the receiving language, namely the orthographic, phonological, morphological and semantic levels. The methodology has for the most part been in line with that described in Filipović 1990. The work also includes a brief discussion of pseudoanglicisms, ellipsis, cases of hypercorrection, etc. The most conspicuous phenomenon at the orthographic level is the large number of loans that keep the English spelling. An origianl Swedish spelling has been established for about 30% of the loans in my corpus, based either on the pronunciation of the English model, on the joint influence of the English pronunciation and spelling, or - only very rarely - showing the influence of an intermediary language. Another interesting point is the large number of orthographic variants. Numerous variants are characteristic of the phonological level as well. The corpus offers examples of all the three forms of transphonemization (zero, compromise and free), which are all plentifully illustrated in this work. Changes in the place and type of accent are also discussed and illustrated. The chapter on morphology contains a detailed discussion of word formation phenomena by part of speech (suffixes involved, type of transmorphemization). Compounds have been found to follow the same basic principles as simple words, except that they offer the possibility of hybrid formation - amply exploited in Swedish. The second part of this chapter discusses various grammatical categories and their markers (gender, plural, conjugation, etc.). The semantic analysis focuses on changes in semantic extension. Restriction in the number of meanings and zero extension are singled out as by far the most common phenomena. Examples of restriction in the field and the two types of the expansion of meaning are also quoted, and it is suggested that all of them can occur during the process of primary adaptation.